2015
DOI: 10.1159/000381854
|View full text |Cite
|
Sign up to set email alerts
|

Population Growth and Allergen Content of Cultured <b><i>Euroglyphus maynei</i></b> House Dust Mites

Abstract: Background: The house dust mite, Euroglyphus maynei, occurs in homes worldwide and is an important source of many allergens. Many patients sensitive to Dermatophagoides farinae and D. pteronyssinus are also sensitive to E. maynei. Extracts to detect sensitivity to E. maynei and reagents to detect E. maynei allergens in the environment or in cultures are not readily available. Information for the culture of E. maynei and for the determination of allergen and endotoxin levels in cultures is limited. Method: We m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Mite-rearing condition in our system is under the temperature in range of 25–30 °C with 75–80% humidity. With the indicated ambient, mite population becomes mature in approximately 4–6 weeks, which is rather shorter when compared with those of the conditions in the western countries. It has been documented that maximum growth phase provides not only the highest amount of live mites but also the allergen concentration, , and hence we use mature mites for source of material for allergenic extract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mite-rearing condition in our system is under the temperature in range of 25–30 °C with 75–80% humidity. With the indicated ambient, mite population becomes mature in approximately 4–6 weeks, which is rather shorter when compared with those of the conditions in the western countries. It has been documented that maximum growth phase provides not only the highest amount of live mites but also the allergen concentration, , and hence we use mature mites for source of material for allergenic extract.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Der f 10, which was minor allergen among the Korean patients, gave IgE binding to sera of 75% of the 20 Thai patients. Several publications reported that the culturing temperature and culture media influences the rate of mite-population growth, allergen production, and the ratio of allergens in extracts made from cultured mites. ,, This might explain the dissimilar results and immuno-proteomics. Moreover, identification and characterization of HDM allergens using new approaches like genomic and transcriptomic techniques could reveal 20 canonical allergens and 7 noncanonical allergen homologues including novel allergen, ubiquinol-cytochrome c reductase binding protein-like protein designated Der f 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The strain of E . maynei that was chosen for genome sequencing is a long-standing laboratory reference culture that originated in Galveston, TX, USA, and has been maintained as a randomly-breeding population for over 20 years [ 5 , 20 ]. Genomic DNA was isolated from a pool of living mites (~20 mg wet weight) using the Wizard SV genomic DNA purification system (Promega, Madison, WI) and the manufacturer’s animal tissue protocol.…”
Section: Methodsmentioning
confidence: 99%